2005
DOI: 10.1016/j.tcs.2004.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Optimal oblivious routing on d-dimensional meshes

Abstract: In this work we consider deterministic oblivious k-k routing algorithms with buffer size O(k). We present an asymptotically optimal O(k √ n d ) step oblivious k-k routing algorithm for d-dimensional n × · · · × n meshes of n d processors for all k 1 and d > 1. We further show how the algorithm can be used to achieve asymptotically optimal oblivious k-k routing algorithms on other networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In [4,10,12] oblivious weakly-dimensional 1-1 routing algorithms are considered. In [4] it was shown that any oblivious elementary-path 1-1 routing algorithm on M 3,n needs Ω(n 2 ) steps.…”
Section: Definition 26 (Strongly-dimensional) An Oblivious Routing Amentioning
confidence: 99%
“…In [4,10,12] oblivious weakly-dimensional 1-1 routing algorithms are considered. In [4] it was shown that any oblivious elementary-path 1-1 routing algorithm on M 3,n needs Ω(n 2 ) steps.…”
Section: Definition 26 (Strongly-dimensional) An Oblivious Routing Amentioning
confidence: 99%